Nongenetic evolution of the tumor: from challenges to new therapeutic opportunities - Elisa Oricchio (Molecular Oncology)
The ability of cancer cells to change and adapt poses a critical challenge to identifying curative solutions. Tumor evolution has been extensively studied from a genetic perspective, to guide clinicians in selecting the most appropriate therapeutic option based on a patient's mutational profile. However, several studies reported that tumors can evolve toward more aggressive stages or become resistant to therapies without changing their genetic makeup. Indeed, several cell‐intrinsic and cell‐extrinsic mechanisms contribute to tumor evolution. In this viewpoint, I focus on how chromatin, epigenetic, and transcriptional changes contribute to tumor evolution, allowing cancer cells to transition to different cell states and bypass response to therapies. Although tumor nongenetic evolution is harder to trace and predict, understanding its principles might open new therapeutic opportunities.